AHMAD SIRHINDÄª DAN PEMBAHARUAN TAREKAT - Rohman, Fathur (Kopertais Wilayah X Jawa Tengah, 2014)
AbstractThere is an understanding that some of sufi orders to find haqi>qah through the sufi tari>qah no longer need the shari>âah. Shari>âah is seen as the outer skin of religion, and haqi>qah is the core. Because of getting the core of religion, the skin has no use anymore. This understanding is a rasionable understanding of the sufi mystics of the past that most no longer pay attention to the rules of shari>âah in its suluk. Most sufis, at that time, preferred a more philosophical sufism which emphasize thinking to achive rather than the worship of god and morality. It can be seen from the popularity of the doctrine of wahdat al-wuju>d which so dominates the teaching of classical sufism. This phenomenon invites the attention of Ahmad Sirhindi, on of sufi and mursyid of naqshabandi order. He moved to reform of the sufi orders who was then filled with heretical practices and doctrines which dominated wahdat al-wuju>d. This study aims to discover and develop ideas of Sirhindi to reform the sufi orders. This research is a qualitative form of research library in using the instrument, so that the resulting data are in the form of data analysis, presentation and writing of the main source, namely al-Maktu>bat thatâs magnum opus of Sirhindi. This study is descriptive-exploratory study. The data analysis technique used in this study was content analysis. The results of this study revealed that are some basic things are the focus sirhindi in revision, among others: first, the synchronization shari>âah, tari>qah, and haqi>qah; second, purification sufi orders of deviant practices; third , rejection of the theory of wahdat al-wuju>d; fourth, applying the theory wahdat al-shuhu>d.Â Keywords: Sufism, Sufi orders, Reform, Sirhindi.",